2015
DOI: 10.1039/c5ra08688d
|View full text |Cite
|
Sign up to set email alerts
|

Applications of HRP-immobilized catalytic beads to the removal of 2,4-dichlorophenol from wastewater

Abstract: 4-Dichlorophenol, as a highly toxic pollutant, widely exists in wastewater discharged from several industries. In this work, the use of immobilized horseradish peroxidase for 2,4-dichlorophenol removal from wastewater was investigated. Sodium hydroxide and hydrochloric acid treated PAN-based beads were modified with ethanediamine and chitosan, and then were activated with glutaraldehyde. The enzyme was immobilized onto the activated beads by covalent crosslinking. The surface of the immobilized bead was observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 41 publications
3
18
0
Order By: Relevance
“…From the figure, the immobilized horseradish peroxidase was capable of removing phenol maximally at pH 6.0 (pH 5.0 for free enzyme), and the immobilized enzyme could remove a higher percentage of phenol over a wide range of buffers of varying pH, compared to free enzyme. The reason for this difference may be that many amino acid groups and/or the active centres were bared because of the changes in the structures of the immobilized enzyme . In addition, the removal efficiency of phenol decreased inordinately at other pH levels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the figure, the immobilized horseradish peroxidase was capable of removing phenol maximally at pH 6.0 (pH 5.0 for free enzyme), and the immobilized enzyme could remove a higher percentage of phenol over a wide range of buffers of varying pH, compared to free enzyme. The reason for this difference may be that many amino acid groups and/or the active centres were bared because of the changes in the structures of the immobilized enzyme . In addition, the removal efficiency of phenol decreased inordinately at other pH levels.…”
Section: Resultsmentioning
confidence: 99%
“…In light of the serious effects on health and environment, removing phenols from high‐strength phenolic wastewater is of great importance. Horseradish peroxidase, a widely researched enzyme, has been successfully used to remove phenolic compounds (such as phenol, p‐chlorophenol, 2,4‐dichlorophenol) from different solutions . HRP possesses a heme cofactor with a distal and proximal histidine on either side, and it catalyzes the oxidatives of phenolic compounds to their corresponding oligomers and insoluble polymers when activated by H 2 O 2 .…”
Section: Introductionmentioning
confidence: 99%
“…10 Thus, the maximum catalytic activity at pH 7.0 suggests that the optimal performance was not due to an enhanced substrate activity or hemin activation, but is indicative of the HRP-like character of the prepared catalyst, which is consistent with the optimal pH of HRP (6.0-7.2). [24][25][26] The pH-dependent activity of the HRP-mimetic catalyst suggests the anionic cysteinate coordination to Fe(III) of hemin, which is common for many metalloproteins. 21 Under acidic conditions, the cysteinate is protonated to form neutral cysteine that weakly binds Fe(III).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, a combination of chemical and enzymatic wastewater remediation methods was also shown to be effective in further increasing the efficiency of individual treatment approaches, and completely detoxifying and removing different recalcitrant pollutants from the various effluents. Some studies suggested that homogenous enzymes are more efficient than heterogeneous reaction systems [150], while other investigations reported an opposite observation [126]. These differences in the obtained results might be according to various operating conditions (i.e., enzyme concentration, treatment time and source of enzyme) used in these two studies.…”
Section: Unresolved Challenges Concluding Remarks and Future Outlooksmentioning
confidence: 87%